Commentary on Polak How short is the shortest metric subdivision? - Friberg, Anders (Empirical Musicology Review, 2018)
This commentary relates to the target paper by Polak on the shortest metric subdivision by presenting measurements on West-African drum music. It provides new evidence that the perceptual lower limit of tone duration is within the range 80-100 ms. Using fairly basic measurement techniques in combination with a musical analysis of the content, the original results in this study represents a valuable addition to the literature. Considering the relevance for music listening, further research would be valuable for determining and understanding the nature of this perceptual limit.